2019
DOI: 10.1039/c9pp00223e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectroscopy and QM/MM simulations of a biomimetic ultrafast light-driven molecular motor

Abstract: A molecular motor potentially performing a continuous unidirectional rotation is studied by a multidisciplinary approach including organic synthesis, transient spectroscopy and excited state trajectory calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…Such a chiral version of the above demethylated compound, i.e. Ch-dMe-MeO-NAIP, has been reported separately [34] and behaves like its achiral version, i.e. according to photoisomerization scenario II.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Such a chiral version of the above demethylated compound, i.e. Ch-dMe-MeO-NAIP, has been reported separately [34] and behaves like its achiral version, i.e. according to photoisomerization scenario II.…”
Section: Introductionmentioning
confidence: 88%
“…[31][32][33] Consequently, chiral NAIP compounds have been synthesized to explore their applications as light-driven molecular motors. [34] In this paper, we review and expand our UV-Vis transient absorption (TA) spectroscopy investigations of the photoreactivity of the set of IP compounds displayed in Figure 1A, with a special focus on photoisomerization QYs. The methodology used for determining and comparing the absolute QYs of all compounds is reported in Section II.…”
Section: Introductionmentioning
confidence: 99%
“…In Eqs. (12) and (13) the symbol H stands for the Heaviside step function, that is equal to 1 if its argument is The overestimation -with respect to the quantum results -of the probability of forming the trans-PSB3 product in S 0 at around 80 fs, i.e., immediately after reaching the intersection space region at about 50 fs delay, is common to all quantum-classical methods. 3 It appears that trajectories are funneled through the intersection space at a higher rate than the quantum wavepacket, resulting in a significantly overestimated quantum efficiency at short time scales.…”
Section: Probabilities and Quantum Yieldmentioning
confidence: 99%
“…Due to its ultrafast speed and photobiological role, the rPSB11 isomerization has been studied for many years experimentally [3][4][5][6][7] and computationally. 5,[7][8][9][10][11][12] Atomistic simulations of the light-induced reaction dynamics of rPSB11 in Rh using ab initio electronic structure calculations [13][14][15][16][17][18][19][20] have been accessible since 2 the early 2000s accounting for the effect of the protein environment via hybrid quantummechanics/molecular-mechanics (QM/MM) methods.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental and theoretical studies on the AT and 13C isomers ASR and its mutants have identified both effects, and how they are brought about by point mutations. For the photoswitches, steric [118] and electronic [20,123] effects, brought about by substitutions of the NAIP framework were investigated experimentally. These studies showed, in addition tothe change in ESL, a clear influence on the survival of vibrational coherences in the ground state.…”
Section: Towards a Rational Prediction Of The Excited State Lifetimentioning
confidence: 99%